Svenska kyrkan efter millennieskiftet - Straarup, Jørgen (Religionsvidenskabeligt tidsskrift, 2015)
Since the year 2000, the Church of Sweden is no longer a function within the Swedish state. It has become a free denomination which actualizes several borderland changes in the Swedish model of religion. The dissolution of the relationship with the state has been discussed and prepared for many years, and it became a reality at the turn of the millennium. The need for a defined relationship with the state or an interface, however, has not diminished, since the Church of Sweden is still the largest popular movement in the country. This change in relation has lead to an intensified cooperation between the Church of Sweden and other churches and denominations.